The Missing Professional Perspective: Medical, Veterinary, and Dual Degree Public Health Student Perceptions of One Health - Roopnarine, Rohini; Boeren, Ellen; Regan, Julie-Anne (Frontiers in Public Health, 2021)
Introduction: One Health (OH) is an important concept to design appropriate public health responses to emerging diseases such as COVID-19. How trainee health professionals understand this concept is important to its implementation. In this study, we explored how medical (MD), veterinary (DVM), and dual degree MD and DVM Master of Public Health (MPH) students define OH and its relevance to practice. Methods: Students participated in a survey that included the Readiness for Interprofessional Learning Scale (RIPLS), and two questions requiring them to define and explain the relevance of OH. The transcripts of the OH responses underwent thematic analysis. Role theory was used to explain the variation in how students from these different programmes viewed the concept. Results: The responses of the MD and DVM students in contrast to the dual degree MPH students reflected gaps in their understanding of the concept that pertained to the specific health impacts of global warming; antimicrobial resistance, food security; social, cultural and environmental determinants of zoonoses occurrence, and health policy formation. Discussion: Mitigation of the global risks to public health require a collaborative approach by health professionals. Our findings suggest that MD and DVM students are unaware of many factors that impact patient health outside of their own discipline. The inclusion of dual degree students revealed novel insights that undertaking an MPH may have enabled them to be more aware about the interdisciplinary relevance of OH to their professional practice. We recommend that structured incorporation of OH should inform future medical and veterinary curricula.